Mobile Location-Based Gaming as Driver for Location-Based Services (LBS) - Exemplified by Mobile Hunters - Lonthoff, J.; Ortner, E. (Informatica)
Mobile Location-Based Gaming as Driver for Location-Based Services (LBS) - Exemplified by Mobile Hunters